On the Natural History of Flavin-Based Electron Bifurcation - Baymann, Frauke; Schoepp-Cothenet, Barbara; Duval, Simon; Guiral, Marianne; Brugna, Myriam; Baffert, Carole; Russell, Michael J.; Nitschke, Wolfgang (Frontiers in Microbiology, 2018)
Electron bifurcation is here described as a special case of the continuum of electron transfer reactions accessible to two-electron redox compounds with redox cooperativity. We argue that electron bifurcation is foremost an electrochemical phenomenon based on (a) strongly inverted redox potentials of the individual redox transitions, (b) a high endergonicity of the first redox transition and (c) an escapement-type mechanism rendering completion of the first electron transfer contingent on occurrence of the second one. This mechanism is proposed to govern both the traditional quinone-based and the newly discovered flavin-based versions of electron bifurcation. Conserved and variable aspects of the spatial arrangement of electron transfer partners in flavoenzymes are assayed by comparing the presently available 3D structures. A wide sample of flavoenzymes is analyzed with respect to conserved structural modules and three major structural groups are identified which serve as basic frames for the evolutionary construction of a plethora of flavin-containing redox enzymes. We argue that flavin-based and other types of electron bifurcation are of primordial importance to free energy conversion, the quintessential foundation of life, and discuss a plausible evolutionary ancestry of the mechanism.